Intelligent Assistive Technology Ethics for Aging Adults: Spiritual Impacts as a Necessary Consideration - Trothen, Tracy J. (Religions, 2022)
Potential spiritual impacts of Artificial Intelligence (AI) driven Assistive Technologies (AT) for older adults are absent in most ethics conversations. Intelligent Assistive Technology (IAT) is the term used to describe the spectrum of Assistive Technologies that use AI. In this theoretical essay, I begin by introducing examples of AT and IAT for older adults with age-related disabilities. I argue that spirituality is a marginalized value in ethics that must be considered if IAT ethics is to address the whole person. Some of the potential spiritual impacts of IATs will be suggested through engagement with three core spiritual needs. I ask how IAT might impact these three core spiritual needs. This is not meant to be an exhaustive study of the spiritual impacts of AT. Through the engagement of one approach to spiritual needs, this article proposes that IAT ethics issues intersect with the spiritual needs of aging adults and, therefore, that potential spiritual impacts ought to be addressed as part of IAT ethics for older adults.